STUDI KASUS PERILAKU KONSUMEN DALAM PEMBELIAN PRODUK DAGING AYAM POTONG DI “PRIMA FRESHMART” DESA SETIA MEKAR, KABUPATEN BEKASI - Budiyono, Haris; Rahmanto, M. Ikhwan; Riyan Hartono, Fawaz; Ardisela, Dawud (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2023)
“Prima Freshmart” is a specialty store whose job is to offer several products for kitchen needs, such as chicken meat, eggs, frozen food, and other food and beverages at affordable prices. This research is to find out: (1) The influence of service variable has an effect on the decision to buy beef chicken at "Prima Freshmart". (2) The effect of the product variable on the purchase decision of broiler chicken at "Prima Freshmart". (3) The effect of the price on the decision to buy chicken pieces at "Prima Freshmart". (4) The effect of promotion has an effect on purchasing decisions of chicken pieces at "Prima Freshmart". (5) The influence of location has an effect on the decision to buy chicken pieces at "Prima Freshmart". (6) Service, product, price, promotion, and location on the decision to buy chicken pieces at "Prima Freshmart". This study uses survey methods and the data analysis used is descriptive analysis and multiple linear regression analysis. The results of this study indicate that the relationship between service, product, promotion, price, and location on purchasing decisions is 0.827, meaning that the value of a positive relationship and the value of the coefficient of determination is 68.4% with the equation value Ŷ = 0,978-0,380X1 + 0,369X2 + 0,773X4. Variables of service, product, price, promotion, and location have a joint effect on the decision to buy chicken at "Prima Freshmart". Product, price, and promotion variables have a partial effect on the decision to purchase chicken pieces at "Prima Freshmart".